Transmission mode of a deformable diffraction grating with a refracting fluid layer - Guerrero, Raphael A (Archīum Ateneo, 2017)
We fabricate a deformable elastomeric grating by soft lithography and add a fluid layer. Tunable diffraction output as a function of applied strain is modified by refraction through the fluid. Using a water layer, the diffraction angle is tuned from 37.8° to 33.1° with an applied strain of 18%. Experimental results are accurately described by the combined effects of diffraction by a deformable grating and refraction by a fluid with a curved surface.